Bullous Pemphigoid: Use of C4d Immunofluorescent Staining in a Case With Repeated Negative Conventional Direct Immunofluorescence Studies. (December 2017) - Kassaby, Sarah S.; Hicks, Alexander; Leicht, Stuart; Youngberg, George A.
Abstract : Abstract: Direct immunofluorescence (DIF) using frozen section material from a fresh/preserved perilesional biopsy is the gold standard for the immunopathologic diagnosis of bullous pemphigoid (BP). DIF in BP shows linear dermoepidermal junction (DEJ) staining for C3, with or without staining for IgG. In some situations, only a formalin-fixed lesional biopsy is obtained (with no fresh/preserved perilesional biopsy for DIF). In this setting, paraffin section C4d immunohistochemistry has proven to be diagnostically useful, demonstrating linear DEJ positivity for C4d. We present a novel use of C4d staining for the diagnosis of BP, specifically analyzing C4d perilesional frozen section DIF in a case where standard perilesional frozen section DIF for IgG/C3 was available, but was negative. An 80-year-old woman presented with a pruritic bullous lesion on her left upper extremity, clinically thought to represent BP. Lesional histologic findings were typical for BP, but perilesional frozen section DIF staining was negative for IgG and C3. A second set of biopsies processed at a different laboratory yielded the same result. A diagnosis of bullous scabies was considered. Subsequently, perilesional frozen section DIF for C4d was obtained, which showed strong linear DEJ positivity, confirming the diagnosis of BP. DIF for C4d is widely used in transplant pathology, since C4d is persistent in tissue, versus C3. Our case demonstrates that perilesional frozen section DIF staining for C4d may be positive and diagnostic in BP, even when conventional DIF staining for IgG and C3 is negative.